Construction and validation of a distance Basic Life Support Course - Isabel Karolyne Fernandes Costa; Manuela Pinto Tibúrcio; Gabriela de Sousa Martins Melo; José Eugênio Lopes Leite; Rodrigo Assis Neves Dantas; Gilson de Vasconcelos Torres
ABSTRACT Objective: to describe the content construction and validation process of the Distance Education Basic Life Support Course. Method: methodological study, developed through literature review, outlined in the light of the Bloom's Taxonomy and Ausubel's Meaningful Learning Theory. For validation, the analysis was performed with judges, using a structured tool. Results: the construction of the distance course was complex and challenging, since it was tried to develop it with logical-methodological coherence, considering the constructivist perspective, representing an advance in the process of dissemination of the Urgency and Emergency teaching culture. As for the content validation process, it was verified that of the 16 suggestions made by the judges, 14 were accepted and two rejected. Conclusion: the course had its contents validated by experts.